Is the "Human Reproductive System" Interactive Learning Video Appropriate for Equality Education Programs? - Sudira, Habib; Ibrahim, Nurdin; Priyono (Journal of Education Reseach and Evaluation, 2023)
Distance learning impacts students, such as learning outcomes and learning interests. Learning outcomes during distance learning and face-to-face learning have differences. The learning materials used by Package B program students during distance learning are only in the form of e-modules. Natural Sciences (IPA) subjects, especially "Human Reproductive System," are Package Program students’ most difficult material. Interactive learning videos are believed to be one of the effective learning media to improve student learning outcomes, get positive responses from students, and can be used for independent learning. This study aimed to develop an interactive learning video, "human reproductive system," in natural science lessons. This research is development research using the Hannafin and Peck model. Data collection techniques in this study consisted of interviews and questionnaires. Data analysis techniques in this research and development use quantitative and qualitative data analysis techniques. Several conclusions can be drawn based on the research that has been carried out. Audiovisual learning styles dominate students’ learning styles; the age of package B program students ranging from 14 years old to 37 years old; interactive learning videos can overcome the various limitations of experience that package B program students have. Interactive learning videos can be used for almost all topics, types of learning, and every domain starting from cognitive, affective, and psychomotor, positively impacting the learning process.